Delayed rifampin administration in the antibiotic treatment of periprosthetic joint infections significantly reduces the emergence of rifampin resistance - Darwich, Ali; Dally, Franz; Bdeir, Mohamad; Kehr, Katharina; Miethke, Thomas; Hetjens, Svetlana; Gravius, Sascha; Assaf, Elio; Mohs, Elisabeth (Antibiotics, 2021)
Rifampin is one of the most important biofilm-active antibiotics in the treatment of periprosthetic joint infection (PJI), and antibiotic regimens not involving rifampin were shown to have higher failure rates. Therefore, an emerging rifampin resistance can have a devastating effect on the outcome of PJI. The aim of this study was to compare the incidence of rifampin resistance between two groups of patients with a PJI treated with antibiotic regimens involving either immediate or delayed additional rifampin administration and to evaluate the effect of this resistance on the outcome. In this retrospective analysis of routinely collected data, all patients who presented with an acute/chronic PJI between 2018 and 2020 were recorded in the context of a single-center comparative cohort study. Two groups were formed: Group 1 included 25 patients with a PJI presenting in 2018-2019. These patients received additional rifampin only after pathogen detection in the intraoperative specimens. Group 2 included 37 patients presenting in 2019-2020. These patients were treated directly postoperatively with an empiric antibiotic therapy including rifampin. In all, 62 patients (32 females) with a mean age of 68 years and 322 operations were included. We found a rifampin-resistant organism in 16% of cases. Rifampin resistance increased significantly from 12% in Group 1 to 19% in Group 2 (p < 0.05). The treatment failure rate was 16% in Group 1 and 16.2% in Group 2 (p = 0.83). The most commonly isolated rifampin-resistant pathogen was Staphylococcus epidermidis (86%) (p < 0.05). The present study shows a significant association between the immediate start of rifampin after surgical revision in the treatment of PJI and the emergence of rifampin resistance, however with no significant effect on outcome.
Gesehen am 11.11.2021